Effect of the Fexofenadine on the expression of HRH-1 and HRH-4 receptor in Peripheral Blood Mononuclear Cell isolated from children with diagnosed allergy – in vitro study Short communication - Natalia Kordulewska; Anna Cieślińska; Ewa Fiedorowicz; Beata Jarmołowska; Elżbieta Kostyra (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Purpose: Fexofenadine (FXF) is the active metabolite of terfenadine with selective peripheral H1 receptor antagonist activity. FXF is a third-generation antihistamine, non-sedating, rapid and very long acting used in symptoms associated with allergic diseases such as allergic rhinitis, asthma and dermatitis. The pleiotropic effects of histamine are mediated by four types of receptors that belong to the G-protein-coupled receptor family: histamine H1 receptor (HRH-1), histamine H2 receptor, histamine H3 receptor, and histamine H4 receptor. Our hypothesis is that HRH-4 opens new possibility in treatment in allergy diseases and FXF could be the antagonist of both HRH-1 and HRH-4. Methods: We isolated a peripheral blood mononuclear cell (PBMC) from children with diagnosed allergies and healthy – control group and measured the HRH-1 and HRH-4 mRNA gene expression using Quantitive Real-Time PCR. We obtained the results from basal gene expression and after FXF and histamine stimulation. Results: HRH-1 mRNA basal gene expression shows significantly higher, and HRH-4 shows significantly lower expression in allergy group compared to control. In both groups HRH-1 mRNA gene expression was observed as statistically significant increased after histamine stimulation compared to cells not treated, while in HRH-4 only in allergy group we observed statistical increase. FXF successively blocked histamine affinity in HRH-1 mRNA gene expression but not in HRH-4, where we not observed any reaction. Conclusions: Results clearly overturned our hypothesis about the possibility of using FXF to block over-expression HRH-4 and open new way of treatment in allergy diseases.